Fibroblast growth factor 21: An emerging pleiotropic regulator of lipid metabolism and the metabolic network - Li, Shuo; Zou, Tiande; Chen, Jun; Li, Jiaming; You, Jinming (Genes & diseases, 2024)
Fibroblast growth factor 21 (FGF21) was originally identified as an important metabolic regulator which plays a crucial physiological role in regulating a variety of metabolic parameters through the metabolic network. As a novel multifunctional endocrine growth factor, the role of FGF21 in the metabolic network warrants extensive exploration. This insight was obtained from the observation that the FGF21-dependent mechanism that regulates lipid metabolism, glycogen transformation, and biological effectiveness occurs through the coordinated participation of the liver, adipose tissue, central nervous system, and sympathetic nerves. This review focuses on the role of FGF21-uncoupling protein 1 (UCP1) signaling in lipid metabolism and how FGF21 alleviates non-alcoholic fatty liver disease (NAFLD). Additionally, this review reveals the mechanism by which FGF21 governs glucolipid metabolism. Recent research on the role of FGF21 in the metabolic network has mostly focused on the crucial pathway of glucolipid metabolism. FGF21 has been shown to have multiple regulatory roles in the metabolic network. Since an adequate understanding of the concrete regulatory pathways of FGF21 in the metabolic network has not been attained, this review sheds new light on the metabolic mechanisms of FGF21, explores how FGF21 engages different tissues and organs, and lays a theoretical foundation for future in-depth research on FGF21-targeted treatment of metabolic diseases.